Hypercontent Module: Integration of Islamic Values in Physical-Motor Learning for Early Childhood - Miratul Hayati; Sisca Nurul Fadila (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This study aims to develop teaching materials for the integration of Islamic values in early childhood physical motor learning based on hypercontent The subjects in this study are students of the Early Childhood Islamic Education (PIAUD) study programme at UIN Syarif Hidayatullah Jakarta. This research uses the development research (R&D) model of Dick and Carey. The feasibility of assessing the development of teaching materials for the integration of Islamic values in hypercontent-based early childhood physical motor learning is based on the assessment of PAUD material experts, Islamic Religious Education (PAI) material experts, learning design experts, and linguists. As well as for the openness test conducted on 15 PIAUD study programme students. Analysis using qualitative and quantitative data analysis, data collection using interview guidelines, observation of documentation, and questionnaires. The results showed that the development of teaching materials Integration of Islamic values in hypercontent-based early childhood physical motor learning through a series of trials and expert validation, is worthy of use in early childhood physical motor course activities. The readability test shows that this module is easily understood by PIAUD students.